Struggles Against Displacement: A Case Study of Nilgiri Tribes TODA - M. Abishek (International Journal of Rural and Regional Development, 2025)
This research explores the displacement faced by the Nilgiri tribes of southern India, examining both historical and contemporary contexts. Historically, the Nilgiri tribes, including the Todas, Kotas, and Kurumbas, have lived in the Nilgiri Hills for centuries, maintaining distinct cultural practices and agricultural traditions. However, the onset of British colonial rule in the 19th century marked the beginning of their displacement, as the British established tea plantations, appropriating tribal lands. This process of alienation intensified in the post-independence era as government policies favored plantation agriculture, urbanization, and tourism, exacerbating tribal displacement. Contemporary displacement continues to affect the Nilgiri tribes, as they face threats from commercial development, encroachment by non-tribal settlers, and conservation initiatives that restrict access to their ancestral lands. The Nilgiris are increasingly marginalized, losing control over their natural resources, and facing social and economic vulnerability. These displacements have profound socio-political implications, leading to the erosion of cultural identity, loss of traditional livelihoods, and reduced participation in local governance. The research employs a qualitative methodology, using historical analysis, field interviews with tribal leaders and community members, and ethnographic methods to understand the lived experiences of the Nilgiri tribes. The study analyzes archival materials, government reports, and contemporary narratives to trace the trajectories of displacement and its impacts over time. Key findings indicate that the Nilgiri tribes’ displacement is not only a matter of land loss but also involves the breakdown of social structures and cultural practices. The displacement has led to increased dependency on state welfare programs, diminishing tribal autonomy. Furthermore, contemporary policies often neglect the voices of the tribes in decision-making, contributing to their continued marginalization. The research underscores the need for policies that prioritize tribal rights, cultural preservation, and sustainable development to address these ongoing challenges
Keywords: Nilgiri tribes; displacement; indigenous rights; land alienation; tribal struggles